Understanding practitioners’ strategies to handle test smells: a multi-method study - Santana, Railana; Fernandes, Daniel; Campos, Denivan; Soares, Larissa; Maciel, Rita; Machado, Ivan (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
Test smells are poor design and implementation choices that can affect the test code’s understanding and maintainability. Recent studies show the industry is not aware of the test smells concept, while software engineers commonly encounter obstacles to maintain test code. This study investigated test creation and maintenance strategies through developers’ perception of eight test smells types. We surveyed 87 software testers and interviewed eight to understand their view on test smells in practice. Our results show that most participants use manual strategies for creating and maintaining test cases. Based on data captured from software testers’ perspectives, this study contributes with possible directions and treatments to analyze test smells, seeking to understand how the test affects and potential solutions for test smells.